Reducing meat consumption in the USA: a nationally representative survey of attitudes and behaviours. Issue 10 (26th March 2018) - Neff, Roni A; Edwards, Danielle; Palmer, Anne; Ramsing, Rebecca; Righter, Allison; Wolfson, Julia
Abstract: Objective: Excess meat consumption, particularly of red and processed meats, is associated with nutritional and environmental health harms. While only a small portion of the population is vegetarian, surveys suggest many Americans may be reducing their meat consumption. To inform education campaigns, more information is needed about attitudes, perceptions, behaviours and foods eaten in meatless meals. Design: A web-based survey administered in April 2015 assessed meat reduction behaviours, attitudes, what respondents ate in meatless meals and sociodemographic characteristics. Setting: Nationally representative, web-based survey in the USA. Subjects: US adults ( n 1112) selected from GfK Knowledgeworks' 50 000-member online panel. Survey weights were used to assure representativeness. Results: Two-thirds reported reducing meat consumption in at least one category over three years, with reductions of red and processed meat most frequent. The most common reasons for reduction were cost and health; environment and animal welfare lagged. Non-meat reducers commonly agreed with statements suggesting that meat was healthy and 'belonged' in the diet. Vegetables were most often consumed 'always' in meatless meals, but cheese/dairy was also common. Reported meat reduction was most common among those aged 45–59 years and among those with lower incomes. Conclusions: The public and environmental health benefits of reducing meat consumption create a need for campaigns to raise awareness and contribute to motivation for change. These findings provide rich information to guide intervention development, both for the USA and other high-income countries that consume meat in high quantities.